Gyorsfizető rendszerek – A Világ, Európa és Magyarország: INSTANT PAYMENTS - THE WORLD, EUROPE AND HUNGARY - Taczmann, Róbert (Közép-Európai Közlemények, 2019)
Money takes 2300 years of our history and it has changed slowly but continuously all over its time. Out of the total time-frame, the last two centuries catalysed the development most, however, this period still seems moderate compared to its last two decades, when digital money and Instant Payments started to spread. The rapid development of last 20 years has been enabled by technology developments and supported by market needs, paving the road for Internet of Payments, the global network of national Instant Payments Systems. The new services jump start business and meet consumer needs, so that we can take care of our financing wherever and whenever we want. In this paper we review the brief history of money that led us to the use of IPS and digital money, discover the geographical coverage of Instant Payments Systems and discuss the main features of IPS. We look out to the World and Europe to see the planned solutions and systems already in operation, then review the Hungarian solution being developed. The paper also discusses the contribution of IPS to the national eco-systems, showing the most important benefits of it on both customer and economy level. We overview the lessons learnt from the implementations already have gone live in Europe and review the main features and building blocks towards the new Instant Payments Systems of the European Union, TIPS. The Pan-European instant payments system shows us how to build up a continent-wide payments solution in order to get a step closer to a global payment network, Internet of Payments.